<span>2.397 is the answer.
</span>
Answer:
C. ![N(t)=150\cdot 3^t](https://tex.z-dn.net/?f=N%28t%29%3D150%5Ccdot%203%5Et)
Step-by-step explanation:
You are given the exponential function ![n(t)=ab^t.](https://tex.z-dn.net/?f=n%28t%29%3Dab%5Et.)
From the table,
at
thus
![N(0)=a\cdot b^0\\ \\150=a\cdot 1\ [\text{ because }b^0=1]](https://tex.z-dn.net/?f=N%280%29%3Da%5Ccdot%20b%5E0%5C%5C%20%5C%5C150%3Da%5Ccdot%201%5C%20%5B%5Ctext%7B%20because%20%7Db%5E0%3D1%5D)
Also
at
thus
![N(1)=a\cdot b^1=a\cdot b.](https://tex.z-dn.net/?f=N%281%29%3Da%5Ccdot%20b%5E1%3Da%5Ccdot%20b.)
Since
substitute it into the second equation
![450=150\cdot b\\ \\b=\dfrac{450}{150}\\ \\b=3](https://tex.z-dn.net/?f=450%3D150%5Ccdot%20b%5C%5C%20%5C%5Cb%3D%5Cdfrac%7B450%7D%7B150%7D%5C%5C%20%5C%5Cb%3D3)
and the expression for the exponential function is
![N(t)=150\cdot 3^t](https://tex.z-dn.net/?f=N%28t%29%3D150%5Ccdot%203%5Et)
Answer:
![A=-323](https://tex.z-dn.net/?f=A%3D-323)
Step-by-step explanation:
A = (-123)+77+(-257)+23-43
A = -46+(-257)+23-43
A = -303+23-43
A = -280-43
A = -323
Hope this helps
Answer:
A
Simpel use have to use input outpout machine